[A Riporter: Frei Tamás]
Recording of “A Riporter: Frei Tamás”, a show moderated by Tamás Frei, broadcast on RTL Klub in which he documents the life of prosperous and famous people, among which Peter Munk (Canadian businessman and philanthropist) and Paul Soros (private investor, philanthropist and George Soros’ brother). Tamás Frei travels to Toronto and interviews Peter Munk and to New York to discuss with Paul Soros.